Mini-laparoscopic versus robotic radical hysterectomy plus systematic pelvic lymphadenectomy in early cervical cancer patients. A multi-institutional study. Issue 1 (January 2015) - Corrado, G.; Fanfani, F.; Ghezzi, F.; Fagotti, A.; Uccella, S.; Mancini, E.; Sperduti, I.; Stevenazzi, G.; Scambia, G.; Vizza, E.
Abstract Objective The aim of this study was to verify possible differences in terms of perioperative outcomes and complications between mini-laparoscopic radical hysterectomy with lymphadenectomy (mLRH) and robotic radical hysterectomy with lymphadenectomy (RRH) in patients with early cervical cancer (ECC). Material and methods In this retrospective study, thirty women with early stage cervical cancer who underwent mini-laparoscopic radical hysterectomy plus lymphadenectomy (mLRH) were compared with a cohort of thirty women who underwent robotic multiport radical hysterectomy (RRH). The study involved patients, between August 2010 and December 2012, from three Italian institutions: National Cancer Institute of Rome, University of Insubria, Varese, and the Catholic University of the Sacred Heart of Rome. Results No significant differences between groups were observed in terms of age, BMI, previous abdominal surgery or FIGO stage. Operative time, blood loss, need of blood transfusion, risk of intra- and post-operative complications, and lymph nodes yield were similar between mLRH and RRH in patients with ECC. The median length of hospital stay was 2 days in the mLRH group and 3 days in the RRH group (p < 0.05). Conclusions The few differences we registered do not seem clinically relevant, thus making the two procedures comparable. The decision on how to gain best access for radical hysterectomy considers the surgeon's skill and experience with the different possible approaches. Further randomized trials are needed to determine whether mini-laparoscopic techniques truly offer any advantages.